EMOTIONAL LABOUR OF ADDICTION COUNSELOR MOTHERS OF YOUNG CHILDREN - Duwi Puspitasari; Beny Rahim; Ayu Ulivia; Marlita Andhika Rahman (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
Addiction counselors are required to regulate their emotions while providing rehabilitation services to clients with complex psychological conditions. These emotional demands become more challenging when counselors simultaneously fulfill the roles of mothers with young children and spouses in long-distance marriages. This study aimed to explore the emotional labour experiences of addiction counselors managing these multiple roles. A qualitative phenomenological design was employed. Participants were selected through purposive sampling, while data were collected using semi-structured interviews and observations and analyzed through Interpretative Phenomenological Analysis (IPA). The findings revealed that participants experienced substantial emotional labour resulting from overlapping professional and family responsibilities, leading to emotional exhaustion, role conflict, and increased parenting burdens. To maintain professional performance, participants adopted various emotion regulation strategies, including compartmentalization, emotional self-awareness, positive self-affirmation, and religious coping. Family support, partner involvement, coworker assistance, and organizational flexibility emerged as important protective factors that strengthened resilience and enabled participants to sustain high-quality counseling services despite ongoing work–family demands.